Method for preparing concrete early-strength quick-setting additive from hazardous waste aluminum ash
By mixing hazardous waste aluminum ash with sodium carbonate and calcining it with other additives, early strength and fast coagulation additives are prepared, which solves the problems of waste of aluminum resources and environmental pollution, and at the same time significantly improves the early strength and condensation speed of concrete.
Patent Information
- Application Number
- CN202411988304.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-15
AI Technical Summary
The existing technology is difficult to effectively utilize solid waste electrolytic aluminum ash, resulting in waste of aluminum resources and environmental pollution. At the same time, the early strength of existing concrete repair materials is insufficient, making it difficult to meet the needs of rapid repair infrastructure.
By mixing and calcining hazardous waste aluminum ash with sodium carbonate, an aluminum ash fluorosilicate slurry mixture is prepared, and mixed with polyvinyl alcohol, wetting agent and anti-deposition agent, drying and grinding, to obtain a premature fast-coagulation additive.
The hazardous waste aluminum ash is treated harmlessly and converted into an efficient concrete early strength and fast-setting agent, which significantly reduces the concrete settling time and improves early strength, solving the problems of waste of aluminum resources and environmental pollution.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of concrete additives, and in particular relates to a method for preparing a concrete early strength and rapid setting additive by utilizing hazardous waste aluminum ash. Background Art
[0002] With the rapid development of my country's economy, new requirements have been put forward for the construction of infrastructure such as roads, bridges, and tunnels. The heavy traffic load, increased traffic density, and higher driving speed have accelerated the damage of some transportation facilities, making the maintenance of cement concrete infrastructure more and more severe. Research on rapid repair materials with excellent performance will make a huge contribution to society.
[0003] Solid waste electrolytic aluminum ash is a kind of scum floating on the aluminum liquid in the electrolytic cell during the aluminum electrolysis process. In addition to valuable aluminum resources such as metal aluminum and aluminum oxide, it also includes a small amount of harmful substances such as fluoride salts. At present, the domestic method of processing aluminum ash is generally to extract the high-content aluminum by physical methods, and then abandon the remaining aluminum ash and aluminum ash slag for landfill or storage, which not only causes a waste of aluminum resources, but also causes serious pollution to the surrounding environment; therefore, the recovery and utilization of solid waste electrolytic aluminum ash is of great significance to environmental protection, efficient utilization of resources and sustainable economic development. Summary of the invention
[0004] An object of the present invention is to solve at least the above problems and / or disadvantages and to provide at least the advantages which will be described hereinafter.
[0005] In order to achieve these purposes and other advantages according to the present invention, a method for preparing a concrete early strength and quick setting additive using hazardous waste aluminum ash is provided, comprising:
[0006] Step 1: Evenly mix hazardous waste aluminum ash and sodium carbonate, then calcine them, and then cool the calcined aluminum ash;
[0007] Step 2: Moisten the calcined aluminum ash with water, then slowly add fluorosilicic acid, and stir thoroughly to obtain an aluminum ash fluorosilicic acid slurry mixture;
[0008] Step 3: Mix the aluminum ash fluorosilicic acid slurry mixture with polyvinyl alcohol, then add a wetting agent and an anti-settling agent, stir, and then dry and grind to obtain an early strength and quick setting additive.
[0009] Preferably, in the step 1, the mass ratio of hazardous waste aluminum ash to sodium carbonate is 100-150:30-70, the calcination temperature is 850-1050° C., and the calcination time is 2-12 hours.
[0010] Preferably, in step 2, the mass ratio of calcined aluminum ash, water and fluorosilicic acid is 1-1.5:1-1.5:2-4.5, the concentration of fluorosilicic acid is 15-40wt%, and the stirring reaction time is 1-4h.
[0011] Preferably, in step three, the mass ratio of the aluminum ash fluorosilicic acid slurry mixture, polyvinyl alcohol, wetting agent and anti-settling agent is 100:1-3:1-5:1-3.
[0012] Preferably, in step three, the wetting agent is one or more of polyether-modified polysiloxane, isomeric decanol ether, polypropylene glycol, sulfonated oil, ethanol, propylene glycol, polyoxyethylene alkylphenol ether or polyoxyethylene fatty alcohol ether.
[0013] Preferably, in step 3, the anti-settling agent is one or more of hydrated magnesium silicate, polyacrylamide, modified organic bentonite, modified hydrogenated castor oil, attapulgite clay powder, diatomaceous earth, magnesium aluminum silicate or nano aluminum hydroxide.
[0014] Preferably, in step three, stirring is performed for 10 to 60 minutes, the grinding speed is 1000-3000 rpm, and the grinding time is 10-30 minutes.
[0015] Preferably, after obtaining the calcined aluminum ash in step 1, the calcined aluminum ash is modified by:
[0016] S1, dissolving calcined aluminum ash in water, then adding calcium oxide, stirring and reacting for a period of time, then adding amino acid to the solution for reaction, and drying after the reaction is completed to obtain a solid powder;
[0017] S2. Dissolve triphenyl phosphite in ethanol to prepare a triphenyl phosphite solution, then spray the triphenyl phosphite solution into the solid powder in the form of high-pressure spray, and then heat and stir to remove the solvent to obtain modified calcined aluminum ash.
[0018] Preferably, in S1, the mass ratio of calcined aluminum ash, water, calcium oxide and amino acid is 1-1.5:1-2:0.15-0.25:0.02-0.04, the amino acid is one or more of lysine, arginine and proline, the stirring time is 1-4h, the drying temperature is 80-120°C, and the drying time is 1-4h.
[0019] Preferably, in S2, the concentration of triphenyl phosphite solution is 5-10wt%, the amount of triphenyl phosphite added is 0.5-1wt% of the mass of calcined aluminum ash, the high-pressure spray pressure is 0.5-1.5Mpa, the flow rate is 50-100L / h, the heating and stirring temperature is 100-140°C, and the stirring time is 3-6h.
[0020] The present invention includes at least the following beneficial effects: hazardous waste aluminum ash containing harmful substances can be harmlessly treated, and valuable aluminum resources such as metallic aluminum and aluminum oxide therein can be converted into an early strength and rapid setting agent for concrete, and the prepared early strength and rapid setting agent can effectively reduce the setting time and improve the early strength when used for concrete or cement mortar pouring.
[0021] Other advantages, objectives and features of the present invention will be embodied in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention. DETAILED DESCRIPTION
[0022] The present invention is described in further detail below so that those skilled in the art can implement it according to the description.
[0023] Example 1
[0024] A method for preparing a concrete early strength and quick setting additive using hazardous waste aluminum ash comprises the following steps:
[0025] Step 1: Mix 12 kg of hazardous waste aluminum ash and 4 kg of sodium carbonate evenly, then put them into a rotary kiln, calcine them at 1000°C for 8 hours, and cool the calcined aluminum ash;
[0026] Step 2: add 10 kg of water to 10 kg of calcined aluminum ash to moisten it, then slowly add 30 kg of 40% fluorosilicic acid, and stir thoroughly for 4 hours to obtain an aluminum ash fluorosilicic acid slurry mixture;
[0027] Step 3: Mix 30 kg of aluminum ash fluorosilicic acid slurry mixture and 0.6 kg of polyvinyl alcohol. After mixing evenly, add 0.9 kg of polyether modified polysiloxane and 0.6 kg of polyacrylamide and stir for 60 minutes. After drying, put the mixture into a grinder, grind at 2500 rpm for 2 minutes, and continue to grind at 2000 rpm for 30 minutes to obtain an early strength and quick-setting additive.
[0028] Example 2
[0029] A method for preparing a concrete early strength and quick setting additive using hazardous waste aluminum ash comprises the following steps:
[0030] Step 1: Mix 12 kg of hazardous waste aluminum ash and 4 kg of sodium carbonate evenly, then put them into a rotary kiln, calcine them at 1000°C for 8 hours, and cool the calcined aluminum ash;
[0031] Step 2: add 10 kg of water to 10 kg of calcined aluminum ash to moisten it, then slowly add 30 kg of 40% fluorosilicic acid, and stir thoroughly for 4 hours to obtain an aluminum ash fluorosilicic acid slurry mixture;
[0032] Step 3: Mix 30 kg of aluminum ash fluorosilicic acid slurry mixture and 0.6 kg of polyvinyl alcohol. After mixing evenly, add 0.9 kg of polyoxyethylene alkylphenol ether and 0.6 kg of hydrated magnesium silicate and stir for 60 minutes. After drying, put the mixture into a grinder, grind at 2500 rpm for 2 minutes, and continue to grind at 2000 rpm for 30 minutes to obtain an early strength and quick-setting additive.
[0033] Example 3
[0034] A method for preparing a concrete early strength and quick setting additive using hazardous waste aluminum ash comprises the following steps:
[0035] Step 1: Mix 12 kg of hazardous waste aluminum ash and 4 kg of sodium carbonate evenly, then put them into a rotary kiln, calcine them at 1000°C for 8 hours, and cool the calcined aluminum ash;
[0036] The calcined aluminum ash is then modified by:
[0037] S1, 10kg of calcined aluminum ash was dissolved in 20% water, and then 1.5kg of calcium oxide was added. After stirring for a period of time, 0.3kg of lysine was added to the solution for reaction. After the reaction was completed, it was dried to obtain a solid powder;
[0038] S2, dissolving 0.1 kg of triphenyl phosphite in ethanol to prepare a triphenyl phosphite solution with a concentration of 0.5 wt%, and then spraying the triphenyl phosphite solution into the solid powder in the form of high-pressure spray, the high-pressure spray pressure is 1 MPa, the flow rate is 50 L / h, after the high-pressure spray is completed, the temperature is raised to 120 ° C and stirred for 4 hours, and the solvent is removed to obtain modified calcined aluminum ash;
[0039] Step 2: Add 20 kg of water to 10 kg of modified calcined aluminum ash to moisten it, then slowly add 30 kg of 40% fluorosilicic acid, and stir thoroughly for 4 hours to obtain a modified aluminum ash fluorosilicic acid slurry mixture;
[0040] Step 3: Mix 30 kg of modified aluminum ash fluorosilicic acid slurry mixture and 0.6 kg of polyvinyl alcohol. After mixing evenly, add 0.9 kg of polyoxyethylene alkylphenol ether and 0.6 kg of hydrated magnesium silicate and stir for 60 minutes. After drying, put the mixture into a grinder, grind it at 2500 rpm for 2 minutes, and then continue to grind it at 2000 rpm for 30 minutes to obtain an early strength and quick-setting additive.
[0041] Example 4
[0042] A method for preparing a concrete early strength and quick setting additive using hazardous waste aluminum ash comprises the following steps:
[0043] Step 1: Mix 12 kg of hazardous waste aluminum ash and 4 kg of sodium carbonate evenly, then put them into a rotary kiln, calcine them at 1000°C for 8 hours, and cool the calcined aluminum ash;
[0044] The calcined aluminum ash is then modified by:
[0045] S1, 10kg of calcined aluminum ash was dissolved in 20% water, and then 1.5kg of calcium oxide was added. After stirring for a period of time, 0.3kg of lysine was added to the solution for reaction. After the reaction was completed, it was dried to obtain a solid powder;
[0046] S2, dissolving 0.1 kg of triphenyl phosphite in ethanol to prepare a triphenyl phosphite solution with a concentration of 0.5 wt%, and then spraying the triphenyl phosphite solution into the solid powder in the form of high-pressure spray, the high-pressure spray pressure is 1 MPa, the flow rate is 50 L / h, after the high-pressure spray is completed, the temperature is raised to 120 ° C and stirred for 4 hours, and the solvent is removed to obtain modified calcined aluminum ash;
[0047] Step 2: Add 20 kg of water to 10 kg of modified calcined aluminum ash to moisten it, then slowly add 30 kg of 40% fluorosilicic acid, and stir thoroughly for 4 hours to obtain a modified aluminum ash fluorosilicic acid slurry mixture;
[0048] Step 3: Mix 30 kg of modified aluminum ash fluorosilicic acid slurry mixture and 0.6 kg of polyvinyl alcohol. After mixing evenly, add 0.9 kg of polyoxyethylene alkylphenol ether and 0.6 kg of polyacrylamide and stir for 60 minutes. After drying, put the mixture into a grinder, grind it at 2500 rpm for 2 minutes, and then continue to grind it at 2000 rpm for 30 minutes to obtain an early strength and quick-setting additive.
[0049] Comparative Example 1
[0050] The preparation method of a concrete accelerating agent disclosed in CN111704379A comprises: according to weight, 55 parts of waste aluminum ash, 5 parts of bauxite, 20 parts of soda ash, 8 parts of silica powder, 8 parts of quicklime, and 4 parts of stabilizer, wherein the stabilizer comprises 8 parts of sodium sulfate, 11 parts of potassium carbonate, 25 parts of calcium chloride, 30 parts of medical stone, and 26 parts of triethanolamine; each component is accurately weighed according to the proportion, and then the mixture is conveyed through a conveying system. The mixture is transported to a rotary kiln for calcination; during calcination, the mixture is heated to 200°C at a heating rate of 1.5°C / min and kept warm for 30 minutes; then the mixture is heated to 850°C at a heating rate of 8°C / min and kept warm for 60 minutes; after calcination, the mixture is transported to a cooler and cooled to 55°C at a cooling rate of 25°C / min; the cooled mixture is transported to a ball mill and ball-milled at a ball-milling speed of 280r / min for 2 hours to obtain a concrete accelerating agent.
[0051] The products prepared in Examples 1 to 3 and Comparative Example 1 were mixed with silicate cement, and the early strength and quick-setting additive was 6% of the mass of silicate cement. The setting time was tested according to the experimental conditions of Appendix D of GB / T35159-2017, and the compressive strength was tested according to the experimental conditions of Appendix E of GB / T35159-2017. The test results are shown in Table 1 below.
[0052] Table 1
[0053]
[0054]
[0055] It should be noted that: according to the national standard, the initial setting time of the first-class pure paste is not more than 3min, the final setting time is not more than 8min, the 1d compressive strength of the mortar is not less than 7.0MPa, and the 28d compressive strength is not less than 75%. The initial setting time of the qualified pure paste is not more than 5min, the final setting time is not more than 12min, the 1d compressive strength of the mortar is not less than 6.0MPa, and the 28d compressive strength is not less than 70%. The concrete early strength and rapid setting additive prepared by Examples 1 and 2 of the present invention is significantly better than the product prepared by the prior art of Comparative Example 1 in initial setting time, final setting time and compressive strength, especially in 1d compressive strength. On the basis of Examples 1 and 2, Examples 3 and 4 further modify the calcined aluminum ash. The modified calcined aluminum ash can play a good filling and reinforcement effect, improve the mechanical properties of concrete, and improve its compressive strength; further improve the early strength of the mortar, indicating that the concrete early strength and rapid setting additive prepared by the present invention is significantly improved in early compressive strength when used for concrete pouring.
[0056] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes, and they can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and what is shown and described herein.
Claims
1. A method for preparing a concrete early strength and quick setting additive using hazardous waste aluminum ash, characterized in that: include: Step 1: Evenly mix hazardous waste aluminum ash and sodium carbonate and calcine them, then cool the calcined aluminum ash; Step 2: Moisten the calcined aluminum ash with water, then slowly add fluorosilicic acid, and stir thoroughly to obtain an aluminum ash fluorosilicic acid slurry mixture; Step 3: Mix the aluminum ash fluorosilicic acid slurry mixture with polyvinyl alcohol, then add a wetting agent and an anti-settling agent, stir, and then dry and grind to obtain an early strength and quick setting additive.
2. The method for preparing concrete early strength and rapid setting additive using hazardous waste aluminum ash according to claim 1, characterized in that: In the step 1, the mass ratio of hazardous waste aluminum ash to sodium carbonate is 100-150:30-70, the calcination temperature is 850-1050° C., and the calcination time is 2-12 hours.
3. The method for preparing concrete early strength and rapid setting additive using hazardous waste aluminum ash according to claim 1, characterized in that: In the step 2, the mass ratio of calcined aluminum ash, water and fluorosilicic acid is 1-1.5:1-1.5:2-4.5, the concentration of fluorosilicic acid is 15-40wt%, and the stirring reaction time is 1-4h.
4. The method for preparing concrete early strength and rapid setting additive using hazardous waste aluminum ash according to claim 1, characterized in that: In the step 3, the mass ratio of the aluminum ash fluorosilicic acid slurry mixture, polyvinyl alcohol, wetting agent and anti-settling agent is 100:1-3:1-5:1-3.
5. The method for preparing concrete early strength and rapid setting additive using hazardous waste aluminum ash according to claim 1, characterized in that: In the step 3, the wetting agent is one or more of polyether-modified polysiloxane, isomeric decanol ether, polypropylene glycol, sulfonated oil, ethanol, propylene glycol, polyoxyethylene alkylphenol ether or polyoxyethylene fatty alcohol ether.
6. The method for preparing concrete early strength and rapid setting additive using hazardous waste aluminum ash according to claim 1, characterized in that: In the step 3, the anti-settling agent is one or more of hydrated magnesium silicate, polyacrylamide, modified organic bentonite, modified hydrogenated castor oil, attapulgite clay powder, diatomaceous earth, magnesium aluminum silicate or nano aluminum hydroxide.
7. The method for preparing concrete early strength and rapid setting additive using hazardous waste aluminum ash according to claim 1, characterized in that: In the step three, stirring is performed for 10 to 60 minutes, the grinding speed is 1000 to 3000 rpm, and the grinding time is 10 to 30 minutes.
8. The method for preparing concrete early strength and rapid setting additive using hazardous waste aluminum ash according to claim 1, characterized in that: After the calcined aluminum ash is obtained in step 1, the calcined aluminum ash is modified by: S1, dissolving calcined aluminum ash in water, then adding calcium oxide, stirring and reacting for a period of time, then adding amino acid to the solution for reaction, and drying after the reaction is completed to obtain a solid powder; S2. Dissolve triphenyl phosphite in ethanol to prepare a triphenyl phosphite solution, then spray the triphenyl phosphite solution into the solid powder in the form of high-pressure spray, and then heat and stir to remove the solvent to obtain modified calcined aluminum ash.
9. The method for preparing concrete early strength and rapid setting additive using hazardous waste aluminum ash according to claim 8, characterized in that: In S1, the mass ratio of calcined aluminum ash, water, calcium oxide and amino acid is 1-1.5:1-2:0.15-0.25:0.02-0.04, the amino acid is one or more of lysine, arginine and proline, the stirring time is 1-4 hours, the drying temperature is 80-120° C., and the drying time is 1-4 hours.
10. The method for preparing concrete early strength and rapid setting additive using hazardous waste aluminum ash according to claim 8, characterized in that: In S2, the concentration of triphenyl phosphite solution is 5-10wt%, the amount of triphenyl phosphite added is 0.5-1wt% of the mass of calcined aluminum ash, the high-pressure spray pressure is 0.5-1.5Mpa, the flow rate is 50-100L / h, the heating and stirring temperature is 100-140°C, and the stirring time is 3-6h.
Citation Information
Patent Citations
Concrete accelerator and preparation method thereof
CN111704379A